Sublimation of icy planetesimals and the delivery of water to the habitable zone around solar type stars - Brunini, Adrian (2018)
We present a semi-analytic model to evaluate the delivery of water to the habitable zone (HZ) around a solar type star carried by icy planetesimals born beyond the snow line. The model includes sublimation of ice, gas drag, and scattering by an outer giant planet located near the snow line. The sublimation model is general and could be applicable to planetary synthesis models or N-body simulations of the formation of planetary systems. We perform a short series of simulations to asses the potential relevance of sublimation of volatiles in the process of delivery of water to the inner regions of a planetary system during early stages of its formation. We could anticipate that erosion by sublimation would prevent the arrival of much water to the HZ of protoplanetary discs in the form of icy planetesimals. Close encounters with a massive planet orbiting near the outer edge of the snow line could make possible for planetesimals to reach the HZ somewhat less eroded. However, only large planetesimals could provide appreciable amounts of water. Massive discs and sharp gas surface density profiles favour icy planetesimals to reach inner regions of a protoplanetary disc.